Prevalence and Course of Frailty in Survivors of Critical Illness*. Issue 10 (October 2020) - Brummel, Nathan E.; Girard, Timothy D.; Pandharipande, Pratik P.; Thompson, Jennifer L.; Jarrett, Ryan T.; Raman, Rameela; Hughes, Christopher G.; Patel, Mayur B.; Morandi, Alessandro; Gill, Thomas M.; Ely, E. Wesley
Abstract : Objectives: Little is known about frailty that develops following critical illness. We sought to describe the prevalence of newly acquired frailty, its clinical course, and the co-occurrence of frailty with disability and cognitive impairment in survivors of critical illness. Design: Longitudinal prospective cohort study. Setting: Medical and surgical ICUs at five U.S. centers. Patients: Adult patients treated for respiratory failure and/or shock. Measurements and Main Results: We measured frailty with the Clinical Frailty Scale at baseline (i.e., study enrollment) and at 3 and 12 months postdischarge. We constructed alluvial diagrams to describe the course of frailty and Venn diagrams to describe the overlap of frailty with disability in activities of daily living and cognitive impairment. We included 567 participants a median (interquartile range) of 61 years old (51–70 yr old) with a high severity of illness (Acute Physiology and Chronic Health Evaluation II of 23). Frailty (Clinical Frailty Scale scores ≥ 5) was present in 135 of 567 (24%) at baseline, 239 of 530 (45%) at 3 months, and 163 of 445 (37%) at 12 months. Of those with frailty at 3- or 12-month follow-up, 61% were not frail at baseline. Transition to a worse frailty state occurred in 242 of 530 of patients (46%) between baseline and 3 months and in 179 of 445 of patients (40%) between baseline and 12 months. There were 376 patients with frailty, disability, or cognitive impairment at 3-month follow-up. Of these, 53 (14%) had frailty alone. At 12 months, 276 patients had frailty, disability, or cognitive impairment, 37 (13%) of whom had frailty alone. Conclusions: Frailty is common among survivors of critical illness. In the majority, frailty is newly acquired. Roughly one in seven had frailty without co-occurring disability or cognitive impairment. Studies to understand outcomes of frailty that develops as the result of a critical illness and to identify modifiable risk factors for this potentially reversible syndrome are needed. Abstract : Supplemental Digital Content is available in the text.